Leaf Blight of Mango in Nurseries of Major Mango Growing Areas in Bangladesh and its Management (Microbes and Health, 2016)
Leaf blight of mango in nurseries of major mango growing areas in Bangladesh viz. Rajshahi, Chapai Nawabganj and Dinajpur were investigated. A total of 56 varieties of mango (43, 17 and 17 in Rajshahi, Chapai Nawabganj and Dinajpur respectively) were surveyed, where the mean of % plant infection, % incidence and % severity in Rajshahi were from 3.33 to 33.06, 4.10 to 23.18 and 6.60 to 17.85, respectively. In Chapai Nawabgonj, the % plant infection was 11.11 to 23.33, the % incidence was 10.67 to 23.67 and % severity was 13.89 to 15.29. In Dinajpur, 6.19 to 12.14% plant infection, 6.00 to 15.85% incidence and 5.00 to 13.50% severity were recorded. Antibiotic sensitivity test revealed that most of the isolates of Pseudomonas syringae pv. syringae collected from mango were sensitive to Gentamycin and Erythromycin. Under the net house condition, six different treatments (i) 0.05 % Gentamycin (ii) 0.05 % Erythromycin, (iii) 0.05 % Doxycycline (iv) 0.05 % copper sulphate (v) 2 % BAU-biofungicide and (vi) Control) were used for controlling bacterial leaf blight of mango (Variety: Amropali). BAU-biofungicide was found superior in controlling bacterial leaf blight of mango that increased 8.76% plant height and 47.45% branch but reduced 54.14% disease incidence and 53.13% disease severity over control when applied as foliar spray at 2% followed by 0.05 % copper sulphate and 0.05 % erythromycin.Microbes and Health, January 2015. 4(1): 29-35